Stories of Peranakan culture in Thailand's Andaman cluster provinces - Thippiroon Poomduang; Jantima Kheokao; Pairote Wilainuch (Penerbit Universiti Kebangsaan Malaysia, 2021)
This is a study of how the stories of Peranakan culture in Thailand's Andaman cluster provinces are told. Utilising Berlo’s communication model as the primary research framework, this research elaborates on how the Peranakan culture’s stories are told and how these stories help define the Thai Peranakan cultural identity. The findings indicated that there is a lack of storytellers in the new Peranakan culture to continue and drive culture preservation (sender), stories presented did not contain subject matter that points to the real identity of Peranakan culture (message), the channels of storytelling are not continuous and diverse enough (channel) and the awareness of Peranakan culture is limited (receiver). The Peranakan cultural identity, meanwhile, was elaborated in two ways; the history of the Peranakans and the Peranakans' way of life. It was also discovered that the Andaman cluster province was not where the Peranakan’s culture was originally constructed. Instead it was brought to Andaman by Chinese who were trading, living or studying in Malacca or Penang at that time. These Peranakan’s cultural identity is an assimilation of Chinese, Malay, European, and Thai cultures, as evident in Peranakan food, clothes, architecture, and beliefs and traditions.